Marketing Mix Strategy in Waqf Online Fundraising Platform: An Importance-Performance Analysis - Vitriara Ahsana Nadya; Asep Nurhalim; Mohammad Iqbal Irfany (AL-MUZARA'AH, 2023)
As an Islamic social finance practice, waqf has a considerable potential to develop community following maqashid sharia and SDGs. At IPB University, one of few universities with authority as a nazir, the implementation of waqf from ‘civa to civa’ on campus has huge benefits for the development of their surrounding without having to rely on government funding. This study, using Islamic Economics students as its respondent, tries to formulate a marketing strategy for waqf online fundraising platform employing an Importance Performance Analysis. Results show that there is still a noticeable gap between the potential and realized the value of waqf in this platform and demography, indicating that the performance has yet to reach the select value from respondents. Three attributes of the marketing mix in IPB’s online waqf platform that needed the most attention: social media promotion, mass media promotion, and integration with other fundraising platforms.